(untitled) (International Journal of Engineering and Computer Science, 2015)
Sensor nodes are usually installed in public or unattended environment and secure authentication scheme performs important role among communication in between user, wireless sensor network (WSN) and sensor node as it secures the communication by sweeping the security flaw. Authentication scheme must be developed by using all possible available resources and without compromising any security flaw/risk. This paper proposes an efficient authentication scheme for wireless sensor network, which is based on username password and smart card, and this scheme provides better security in between communicating nodes. Users are able to choose own username and password. This scheme involves registration, login and session key establishment phase. Most of scheme don’t allow to hide username in entire scheme, which may lead to insider attack. This scheme uses the combination of symmetric and asymmetric keys, and maintains the authenticity of nodes using mutual authentication that prevents the network from man-in-middle attack and makes it more secure against other security attacks such as insider attack, password guessing attack, replay attack etc.